Анализ уязвимости криптоалгоритмов в группах кос - Горбенко, И. Д.; Митяева, И. А. (ХНУРЭ, 2011)
In the last decade, a number of public key cryptosystems based on combinatorial group theoretic problems in braid groups have been proposed. These cryptosystems and some known attacks on them are represented in the given work.
Keywords: криптография; криптосистема